The changing global power balance : challenges for European firms - Tulder, Rob van; Fernandes Crespo, Nuno; Corado Simões, Vítor; Fernandes Crespo, Cátia (Emerald Publishing Limited, 2025)
The 2023 conference of the European International Business Academy (EIBA) was held in Lisbon, three decades after the previous EIBA Lisbon conference in 1993. Over this 30-year period, the international business environment changed dramatically, passing through phases of globalisation, increased nationalistic sentiments in a large number of countries, and a 'cascade of crises' or a 'poly-crisis'. Currently, MNEs operate within a changing global power balance, with China and its allies challenging the hegemony of the U.S. and its allies. For European MNEs as well as for policy makers, the world economy is no longer characterized by a clear set of relatively stable enabling global conditions but rather by increased volatility, uncertainty, complexity and ambiguity (VUCA). Volume 19 of the Progress in International Business Research (PIBR) series covers three key vectors: The changing global power balance in the world economy, how to deal with rapid changes in technology and innovation, and how to understand and assess the resulting challenges for Europe. A wide variety of perspectives are presented here, including a chapter from Elisa Ferreira, the European Commissioner for Cohesion and Reforms, who takes stock of the present situation and looks into the future from a European policy perspective. By choosing 'innovation' as a major area of focus, we pay tribute to one of the leading international business authors in that area - and a long-term EIBA member - John Cantwell.
Includes index.
Keywords: International relations.; Globalization.; Geopolitics.; Political Science -- International Relations -- General.; elektronické knihy; electronic books